An uncommon cause of unilateral nasal bleeding - Yadav, Satish; Zhang, Bingqiang (Grande Medical Journal, 2020)
Leeches are segmented worms that belongs to phylum Annelida and Hirudinea subclass. They are commonly found in stream water, land and sea. Leech infestation is seen in people swimming or drinking water inhabited by leech. The most common symptom of nasal leech is unilateral nasal bleeding. In this case report, a ten-year-old Chinese boy went swimming in the river in countryside prior to the incident. On examination, he was found to have a leech in his left nostril. The leech self- extruded after irrigation with 5ml of normal saline. Health workers must be aware of the possibility of a leech as the differential diagnosis for unilateral nasal bleeding, especially in a rural area where leeches are prevalent.